Reduced Intracranial Volume in Fabry Disease: Evidence of Abnormal Neurodevelopment? - Pontillo, Giuseppe; Cocozza, Sirio; Brunetti, Arturo; Brescia Morra, Vincenzo; Riccio, Eleonora; Russo, Camilla; Saccà, Francesco; Tedeschi, Enrico; Pisani, Antonio; Quarantelli, Mario (Frontiers in Neurology, 2018)
Introduction Lysosomal storage disorders are often characterized by abnormal brain development, reflected by a reduction of intracranial volume (ICV). The aim of our study was to perform a volumetric analysis of intracranial tissues in Fabry Disease (FD), investigating possible reductions of ICV as a potential expression of abnormal brain development in this condition. Material and Methods Forty-two FD patients (15 males, mean age 43.3±13.0 years) were enrolled along with thirty-eight healthy controls (HC) of comparable age and sex. Volumetric MRI data were segmented using SPM12 to obtain intracranial tissue volumes, from which ICV values were derived. Results Mean ICV of FD patients was 8.1% smaller compared to the control group (p < 5·10-5). Unlike what typically happens in neurodegenerative disorders, no significant differences emerged when comparing between the two groups the fractional volumes of gray matter, white matter and CSF (i.e. normalized by ICV), consistent with a harmonious volumetric reduction of intracranial structures. Discussion The present results suggest that in FD patients an abnormality of brain development is present, expanding the current knowledge about central nervous system involvement in FD, further emphasizing the importance of an early diagnosis.